FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI IBUMENGIKUTI DETEKSI DINI KANKER SERVIKS MELALUI METODE INSPEKSI VISUAL ASAM ASETAT (IVA) DI KABUPATEN BANYUMAS TAHUN 2012 - Ningrum, Roswati Dani; Fajarsari, Dyah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2013)
Cervical cancer ranks first of all cancer cases by 17,2% in Indonesia. The most effective prevention of cervical cancer  used simple method, fast and cheap cost is the method of IVA. The number of women who followed the methods of IVA in the Banyumas district was declined month after month. To determine the factors that influence motivation of mother to follow cervical cancer early detection through inspection of visual acid acetate (IVA) in the Banyumas regency year 2012. This study was a survey analitic research with cross sectional design. The population of study were all women who follow IVA inspection in Banyumas until July 2011 and taken a sample of 95 mothers. The methods of data analysis used rank spearman test. Knowledge of most mothers in good categories (40,0%), level education of most mother in the middle category (43,2%), most economic status > UMR (80,0%), and high motivation at most (49,5%). Knowledge influrnced mother's motivation to follow the early detection of cervical cancer through IVA (p = 0,000), level of education influenced the mother's motivation to follow the early detection of cervical cancer through IVA (p = 0,001), and economic status influence mother motivation to follow the early detection of cervical cancer through IVA (p = 0,002). Knowledge, education and economic status influenced mothers motivation to follow early detection of cervical cancer through IVA in Banyumas. Women of childbearing age should be more motivated to follow the IVA examination to the risk of cervical cancer can be detected earlier.   Keywords       : knowledge, education, economic status, motivation